ROLLER SHAF; PENGGULUNG KAIN SAJADAH PANJANG BERBASIS MESIN - Saefulloh, Ahmad; Arifin, Samsul; Agustiani, Reni; Hadi Nur Rofik; M. Ghozi Anwar (Steam Engineering, 2024)
The aim of this research is to make a Roller Shaf as an alternative tool for rolling long cloth based on machine technology, namely using an AC electric motor. The method used in this research uses the interactive model R&D method from Miles & Huberman which consists of four components, namely data collection, data reduction, and prototype testing on users. Respondents came from the administrators of mosques and prayer rooms in Palangka Raya who were observed randomly, including the Takmir of the Palangka Raya University Mosque, Amanah Mosque, Flamboyan Mosque, Gede Kalampangan Mosque, Al-Khaidir Badak 22 Mosque, and the Jami' Nurul Islam Mosque in Pasar Besar Palangka Raya, then analyzed using qualitative descriptive. The results obtained were that the Roller Shaf trial was carried out at the Salahuddin Campus Mosque, Palangka Raya University and showed that the Roller Shaf could be used, equipped with a volume speed as a rolling speed controller. The Roller Shaf is made from environmentally friendly materials, equipped with a machine microcontroller from an 8 Volt AC dynamo, and covered with a box that is adjusted to the size of the fabric. The obstacle with the Roller Shaf is the use of an AC dynamo which needs to be adjusted to the length of fabric used. If the fabric is satin, it requires a large dynamo voltage. Future suggestions, this machine can be used by mosques and prayer rooms that use long prayer mats as well as users such as laundry entrepreneurs, batik entrepreneurs, and relevant fabric companies.